A study of the application of bilingual education in a kindergarten based in Abu Dhabi - ALMANSOORI, FATEMA MOHAMMED ABDULRAHMAN (2017)
The purpose of this study is to figure out the effectiveness of bilingual education in government kindergarten. This research focusses on the effectiveness of bilingual education on students’ learning process and the evaluation procedure of both languages. In addition, it shows the importance of the parents’ engagement in their children’s learning. This study was carried out because Abu Dhabi applied a new education system in government schools which focusses on bilingual education and as citizens, we need to see the effectiveness of this new model system to know how to make it better in the future and support our children in their learning journey. The study was done in four months. Different data were collected during this period including, interviews, surveys, questionnaires and case study. These data tools were applied for all staff and students in a kindergarten based in Abu Dhabi. It has been found that bilingual education develops students’ interaction and supports them to follow their own individual learning process. In addition, teacher’s familiarity with bilingual education improves the students’ cognitive skills and parents’ engagement encourages students to learn and achieve higher grades.